RELASI PEMERINTAH DAERAH DAN MASYARAKAT DALAM PENYELESAIAN SENGKETA LAHAN DI KABUPATEN KUANTAN SINGINGI TAHUN 2014-2016 STUDI KASUS SENGKETA LAHAN ANTARA MASYARAKAT DENGANPT. DUTA PALMA NUSANTARA WILAYAH OPERASI KUANTAN SINGINGI - Aldiko Putra; Erman M (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Land dispute case between the community and PT. Duta Palma Nusantara involving communities in four Sub-districts (Benai Subdistrict, Kuantan Mudik Subdistrict, Kuantan Hilir Subdistrict and Kuantan Tengah Subdistrict) gave an understanding that this land dispute was very broad and could potentially cause divisions among the community. Extension of HGU of PT. The DPN became a source of conflict between the community and PT. Besides that, the attitude of PT. The DPN that does not accommodate the demands of the community is also the basis of the problem of land disputes between PT. DPN and community. Settlement of the dispute is deemed not maximal, the presence of the government is precisely after the conflict occurred so that the community feels the government is absent in preventing conflict.This study was conducted with a qualitative approach that focused on the study of the form of disputes, the role of local government and government initiatives in resolving land disputes between communities and PT. DPN in Kuantan Singingi Regency. The theory of relations between government and society is a measure in this study and the concept of land dispute is used to describe the conditions of disputes that occur between the community and PT. Dutapalma Nusantara.The land dispute that occurred between PT. Dutapalma Nusantara and the community in the operational area of Kuantan Singingi Regency belong to factual and juridical disputes. In connection with that, the Kuantan Singingi District Government in its capacity of authority has made persuasive efforts to alleviate conflicts between the community and PT. DPN. Relationships built by the government include mediation efforts between community groups and the company. The role of the Kuantan Singingi District Government in resolving land disputes between the community and PT. Dutapalma Nusantara is considered a minimal role because the community and company do not get legal certainty from the policies taken by the Kuantan Singingi Regency government.Keywords; Relations, Land Disputes, Local Government